Military Sexual Assault, Post-Service Employment, and Transition Preparation among U.S. Military Veterans: New Directions for Research - Pritchard, Adam J. (Victims & offenders, 2024)
Unlike studies of military sexual trauma (MST) among active-duty service members, most studies of veterans with MST have been clinical in nature, focused on estimating population prevalence rates, improving clinical responses or treatments, or have associated MST with subsequent health-related risk behaviors such as alcohol or drug abuse. The present study seeks to broaden our understanding of the corollaries of military sexual assault by considering the relationship between being a survivor of military sexual assault and post-service employment and transition experiences. Using secondary data from a survey of the members of a national organization for post-9/11 veterans, this exploratory study examines bivariate and multivariate relationships between self-reported experiences of military sexual assault and specific post-transition outcomes commonly used as indicators of a successful career transition from military to civilian life including employment status, time from transition to employment, and veterans’ perceptions of being prepared for their transition out of the military. Analysis from this study suggests that military sexual assault is impactful in the domains of employment and transition readiness. This paper’s findings point to a need to consider a range of inter-related social determinants of health and well-being when providing post-service career support for veterans.